Online direct-to-consumer messages about non-invasive prenatal genetic testing. Issue 2 (December 2015) - Farrell, Ruth M.; Agatisa, Patricia K.; Mercer, MaryBeth; Coleridge, Marissa B.
Abstract: Non-invasive prenatal testing (NIPT) has been integrated into clinical care at a time when patients and healthcare providers increasingly utilize the internet to access health information. This study evaluated online direct-to-consumer information about NIPT produced by commercial laboratories accessible to both patients and healthcare providers. A coding checklist captured areas to describe content and assess concordance with clinical guidelines. We found that the information presented about NIPT is highly variable, both within a single website and broadly across all websites. Variability was noted in how NIPT is characterized, including test characteristics and indications. All laboratories offer NIPT to test for common sex chromosome aneuploidies, although there is a lack of consistency regarding the conditions offered and information provided about each. Although indicated for a subset of women at increased risk of aneuploidy, some laboratories describe the use of NIPT for all pregnant women. A subset of laboratories offers screening for microdeletions, although clinical practice guidelines do not yet recommend for general use for this indication. None of the online materials addressed the ethical issues associated with NIPT. This study highlights the need for clear, consistent, and evidence-based materials to educate patients and healthcare providers about the current and emerging applications of NIPT.